The effectiveness of hypertension management in China: a community-based intervention study. (2019) - Zheng, Xiaoguo; Xiao, Feng; Li, Ruili; Yin, Delu; Xin, Qianqian; Yang, Huimin; Yin, Tao; Wang, Lihong; Chen, Bowen
Abstract: Aim: This study aimed to evaluate the effectiveness of hypertension management and analyse the factors associated with blood pressure reduction within China's primary healthcare system. Background: Hypertension is one of the leading risk factors for global disease burden and is strongly associated with cardiovascular diseases. In China, hypertension is a serious public health problem, but few studies have evaluated the effectiveness of hypertension management in China's primary healthcare system. Methods: The study sites were 24 primary healthcare institutions, selected using multistage stratified random sampling method. In each institution, hypertension patients aged at least 35 years who agreed to participate and had no disabilities or mental health problems were enrolled for hypertension management. Participants received comprehensive interventions in the primary healthcare system via a team. After a one-year intervention, data from 6575 hypertension patients were analysed to check the effectiveness of hypertension management and examined factors associated with hypertension control. Findings: There was an overall mean reduction of 4.5 mmHg in systolic blood pressure (SBP) and 1.9 mmHg in diastolic blood pressure (DBP). The blood pressure reduction after one year was greater in rural patients than in urban patients, 6.6 mmHg versus 3.4 mmHg for SBP and 2.6 mmHg versus 1.6 mmHg for DBP, respectively. The hypertension control rate also increased more in rural areas (22.1%) than in urban areas (10.6%) after the one-year intervention. Age, body mass index, region and being in an urban area had a significant negative association with the reduction of SBP ( P < 0.05). Education level and baseline SBP showed a significant positive association ( P < 0.05). Conclusions: Community-based hypertension management by general practitioners was feasible and effective. The effectiveness of hypertension management in rural areas was greater than in urban areas. Intervention strategies should pay more attention to patients in rural areas and western China.